Water-based conductive pressure-sensitive adhesive composition, pressure-sensitive adhesive and product thereof

Through the combination of carboxyl-modified MXene and polyacrylate emulsion, the problems of high cost and poor compatibility of precious metal particles in voltage-sensitive adhesives are solved, and a water-based voltage-sensitive adhesive with high conductivity and environmental protection are achieved, which meets the conductivity and Mechanical performance and environmental protection requirements.

CN119242225APending Publication Date: 2025-01-03CROWN TAICANG ADHESIVE PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411512282.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When using precious metal particles as conductive fillers, existing voltage-sensitive adhesives have high costs and poor compatibility with the matrix resin, resulting in insufficient conductivity and bonding strength. At the same time, the use of organic solvents will pollute the environment.

Method used

The carboxy-modified MXene is combined with polyacrylate emulsion, and the chemical bonding of the carboxy-modified MXene and the crosslinking agent is improved to improve the conductivity and compatibility, and water is used to replace organic solvents, reducing costs and meeting environmental protection requirements.

Benefits of technology

The water-based voltage-sensitive adhesive that achieves high conductivity and conductivity stability, high bonding strength, low cost, and meets environmental protection requirements, balances the conductivity, mechanical properties and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105778300000021
    Figure BDA0005105778300000021
  • Figure BDA0005105778300000031
    Figure BDA0005105778300000031
  • Figure BDA0005105778300000041
    Figure BDA0005105778300000041
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a water-based conductive pressure-sensitive adhesive composition, a pressure-sensitive adhesive and a product thereof. The water-based conductive pressure-sensitive adhesive composition is prepared from the following components in parts by mass: 40 to 60 parts of polyacrylate emulsion, 20 to 35 parts of carboxyl modified MXene, 0.5 to 5 parts of isocyanate curing agent, 2 to 5 parts of cross-linking agent and 0 to 38 parts of deionized water. According to the water-based conductive pressure-sensitive adhesive composition disclosed by the invention, the carboxyl modified MXene and the polyacrylate emulsion are compounded, and the dispersity and the stability of the composition in a water phase can be improved by carboxyl modified on the surface of the MXene; the carboxyl modified MXene is compounded with the cross-linking agent, and the carboxyl modified on the surface of the MXene is used as a bonding site and can be chemically bonded with an organic matrix, so that the compatibility is remarkably improved, an effective conductive channel is constructed, and the conductivity of the pressure-sensitive adhesive is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a water-based conductive pressure-sensitive adhesive composition, a pressure-sensitive adhesive and products thereof. Background Art

[0002] Because pressure-sensitive adhesives have good mechanical properties, wettability and flexibility, and have a simple preparation process and low operating temperature, they are widely used in aerospace electrical equipment, rail transit electrical equipment, integrated circuit (IC) packaging, light-emitting diode (LED) packaging and other fields, especially for the bonding of electronic components of handheld and wearable devices that have developed rapidly in recent years.

[0003] Conductive pressure sensitive adhesives are usually made by adding conductive fillers to the base resin to make them conductive. Their conductivity and mechanical properties are closely related to the content of the conductive fillers, the specific surface area, and the structure of the base resin. General conductive fillers mainly include metal particles (such as copper, aluminum, nickel, and silver), modified carbon black, carbon fiber, metallized glass balls, etc. When metal particles are used as conductive fillers, since the metal particles are added in the form of physical doping, they have poor compatibility with the base resin, which can easily reduce the bonding strength and conductivity of the pressure sensitive adhesive; in addition, some pressure sensitive adhesives contain organic solvents, which will pollute the environment.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The invention provides a water-based conductive pressure-sensitive adhesive composition. The pressure-sensitive adhesive formed by the composition has high conductivity and conductive stability, high bonding strength, no organic solvent is added, and good environmental protection.

[0006] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a water-based conductive pressure-sensitive adhesive composition, comprising the following components:

[0007]

[0008] In a specific embodiment of the present invention, the mass ratio of the carboxyl-modified MXene to the cross-linking agent is (6-10):1.

[0009] In a specific embodiment of the present invention, the carboxyl-modified MXene is mainly prepared by modifying MXene, and the particle size of the carboxyl-modified MXene is 35 to 75 μm.

[0010] In a specific embodiment of the present invention, the preparation method of the carboxyl-modified MXene comprises: adding chloroacetic acid and sodium hydroxide to a MXene suspension in sequence for reaction, and collecting the resulting precipitate after the reaction to obtain the carboxyl-modified MXene;

[0011] Wherein, the mass ratio of the chloroacetic acid to the sodium hydroxide is 1:(1-2).

[0012] In a specific embodiment of the present invention, the isocyanate curing agent includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate.

[0013] In a specific embodiment of the present invention, the crosslinking agent includes an epoxy crosslinking agent and / or an aziridine crosslinking agent. Further, the epoxy crosslinking agent includes an epoxy crosslinking agent containing 2 or more epoxy groups; the aziridine crosslinking agent includes at least one of 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine), trimethylolpropane tris[3-(2-methylaziridinyl) propionate], and pentaerythritol tris(3-aziridinyl)acrylate.

[0014] In a specific embodiment of the present invention, the polyacrylate emulsion comprises the following components:

[0015]

[0016] In a specific embodiment of the present invention, the soft monomer includes at least one of butyl acrylate, 2-ethylhexyl acrylate, ethyl acrylate and n-octyl acrylate; the hard monomer includes at least one of methyl methacrylate and isobornyl (meth)acrylate; and the functional monomer includes at least one of hydroxypropyl acrylate, hydroxyethyl acrylate and acrylic acid.

[0017] The second aspect of the present invention provides a pressure-sensitive adhesive composed of the water-based conductive pressure-sensitive adhesive composition of the first aspect of the present invention.

[0018] The third aspect of the present invention provides a pressure-sensitive adhesive product, which comprises the water-based conductive pressure-sensitive adhesive composition provided by the first aspect of the present invention or is prepared from the pressure-sensitive adhesive of the second aspect of the present invention.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The pressure-sensitive adhesive of the present invention adopts carboxyl-modified MXene and polyacrylate emulsion to compound, and the carboxyl group modified on the surface of MXene can improve its dispersibility and stability in the aqueous phase; and by compounding the carboxyl-modified MXene with a crosslinking agent, the carboxyl group modified on the surface of MXene can serve as a bonding site and can be chemically bonded with an organic matrix, which not only improves compatibility, but also constructs a conductive channel and improves conductive performance;

[0021] (2) The pressure-sensitive adhesive of the present invention uses water instead of organic solvents, which can meet environmental protection requirements; and the cost of carboxyl-modified MXene is lower than that of precious metal conductive particles, which significantly reduces the cost of raw materials. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0023] In the prior art, due to the cost of the conductive filler and the compatibility of the conductive filler with the matrix resin, the conductive adhesive cannot achieve a balance between cost, conductivity, mechanical properties and service life.

[0024] Based on this, the first aspect of the present invention provides a water-based conductive pressure-sensitive adhesive composition, comprising the following components:

[0025]

[0026] The carboxyl-modified MXene used in the aqueous conductive pressure-sensitive adhesive composition of the present invention as a conductive particle has good conductive properties, and no precious metal particles such as silver are used, thereby reducing costs. In addition, the density of the carboxyl-modified MXene is lower than that of the metal conductive particles, and the carboxyl groups modified on the surface of the MXene can make it have good dispersibility in the aqueous polyacrylate emulsion, reduce agglomeration and sedimentation phenomena, and help to exert its conductive properties.

[0027] In addition, by compounding carboxyl-modified MXene with a cross-linker, the carboxyl groups modified on the surface of MXene can serve as bonding sites and chemically bond with the polyacrylate emulsion, thereby improving compatibility while constructing an effective conductive channel and improving conductive properties.

[0028] For example, in different embodiments, in the water-based conductive pressure-sensitive adhesive composition of the present invention, the amounts of the components in parts by mass may be as follows:

[0029] The amount of the polyacrylate emulsion can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two ends thereof;

[0030] The amount of carboxyl-modified MXene can be 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 35 parts or any value between any two ends thereof;

[0031] The amount of the isocyanate curing agent can be 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two ends thereof;

[0032] The amount of the cross-linking agent can be 2 parts, 3 parts, 4 parts, 5 parts or any value between any two ends thereof;

[0033] The amount of deionized water can be 0, 4, 8, 12, 16, 20, 24, 28, 32, 38 or any value between any two ends. Deionized water may not be added to the pressure-sensitive adhesive of the present invention, and deionized water is only used as an optional diluent.

[0034] In a specific embodiment of the present invention, the mass ratio of carboxyl-modified MXene to the cross-linking agent is (6-10) : 1. For example, in different embodiments, the mass ratio of carboxyl-modified MXene to the cross-linking agent can be 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1 or any value between any two end values.

[0035] The crosslinking agent is used to form a bond between the carboxyl-modified MXene and the polyacrylate emulsion. If the amount of the crosslinking agent is too little, the bonding effect is limited and the conductivity is not significantly improved; if the amount of the crosslinking agent is too much, the excessive crosslinking agent will act as a curing agent for the polyacrylate emulsion, resulting in a decrease in the adhesive properties and mechanical properties of the pressure-sensitive adhesive. The present invention regulates the ratio of the carboxyl-modified MXene to the crosslinking agent within the above range, which can balance the conductive properties, adhesive properties and mechanical properties.

[0036] In a specific embodiment of the present invention, the carboxyl-modified MXene is mainly prepared by modifying the MXene. The particle size of the carboxyl-modified MXene is controlled to be 35 to 75 μm, specifically 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 75 μm or any value between the two end values.

[0037] In a specific embodiment of the present invention, the preparation method of the carboxyl-modified MXene is: chloroacetic acid and sodium hydroxide are sequentially added to a MXene suspension for reaction, and the precipitate collected after the reaction is the carboxyl-modified MXene.

[0038] Furthermore, the mass ratio of chloroacetic acid to sodium hydroxide is 1:(1-2), specifically 1:1, 1:1.5, 1:2 or any value between the two end values.

[0039] In actual operation, MXene is prepared by wet chemical etching. A specific method for preparing MXene by wet chemical etching is listed here for illustration, not to limit the preparation method of MXene.

[0040] The preparation of MXene suspension includes:

[0041] (1) Using hydrofluoric acid (HF) as an etchant to etch titanium aluminum carbide (Ti3AlC2);

[0042] (2) The material obtained in step (1) is washed until neutral, the precipitate is collected, dispersed, and centrifuged, and the supernatant is collected to obtain a MXene suspension.

[0043] In the above step (1), since HF is highly volatile and cannot be used directly as a raw material, the present invention can generate it by reacting lithium fluoride (LiF) with hydrochloric acid (HCl), or by other methods, which are not limited thereto.

[0044] Among them, the mass ratio of Ti3AlC2 to LiF can be 1:(0.8-1); the ratio of Ti3AlC2 to HCl can be 1gTi3AlC2 corresponding to 15-25mL hydrochloric acid, and the concentration of hydrochloric acid is 8-10mol / L.

[0045] In the above step (1), the etching temperature can be in a relatively mild range, such as 30-40° C., specifically 30° C., 35° C., or 40° C.; the etching time is generally 24±4 h.

[0046] In the above step (2), deionized water is used for washing the material.

[0047] In the above step (2), the precipitate is first dispersed in anhydrous ethanol and treated with ice bath ultrasound for 2.5 hours; then the precipitate is dispersed in water, and the supernatant is collected after centrifugation to obtain the MXene suspension. Furthermore, the centrifugal speed is 3500-4500rpm, and the centrifugal time is 25-30min. Furthermore, the concentration of the MXene suspension can be adjusted according to actual needs, for example, not higher than 6mg / mL, specifically 1mg / mL, 2mg / mL, 3mg / mL, 4mg / mL, 5mg / mL, 6mg / mL or any value not higher than 6mg / mL and not limited to integer values.

[0048] The MXene conductive particles produced by wet chemical etching have a large number of functional groups on their surface, such as fluorine, hydroxyl, carboxyl, etc.

[0049] The preparation method of carboxyl-modified MXene in the present invention comprises: adding chloroacetic acid and sodium hydroxide to a MXene suspension in sequence under stirring at room temperature, and the precipitate obtained after the reaction is the carboxyl-modified MXene.

[0050] The stirring can be carried out in a conventional manner, such as magnetic stirring, and the stirring time can be 3 to 10 minutes. The reaction temperature is 50 to 70°C, specifically 50°C, 60°C, 70°C or any value between the two ends; the reaction time is 12±4h, such as 8h, 10h, 12h, 14h, 16h. Inert gas protection, such as nitrogen, can be introduced during the reaction.

[0051] The obtained precipitate is first washed with deionized water until it is neutral, and then the precipitate is collected after centrifugation. During the collection process, the particle size of the carboxyl-modified MXene can be controlled to be 35 to 75 μm, specifically 35 μm, 45 μm, 55 μm, 65 μm, 75 μm or any value between the two end values. Adjusting the particle size of the carboxyl-modified MXene within the above range is more conducive to its dispersibility and conductivity.

[0052] The present invention uses chloroacetic acid and sodium hydroxide to perform carboxyl modification on the MXene suspension, so that the hydroxyl and fluorine groups on the surface of the MXene are converted into carboxyl groups, and the carboxyl content on the surface of the MXene is increased, which is beneficial to improving its dispersibility, stability and conductivity, and provides more sites for chemical bonding with the cross-linking agent, which can improve the compatibility of MXene with the organic system and construct an effective conductive channel.

[0053] Furthermore, the mass ratio of the chloroacetic acid to the sodium hydroxide is 1:(1-2), specifically 1:1, 1:1.5, 1:2 or any value between any two end values.

[0054] In a specific embodiment of the present invention, the isocyanate curing agent includes at least one of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), and hexamethylene diisocyanate (HDI), preferably TDI.

[0055] In a specific embodiment of the present invention, the crosslinking agent includes an epoxy crosslinking agent and / or an aziridine crosslinking agent. Further, the epoxy crosslinking agent includes an epoxy crosslinking agent containing 2 or more epoxy groups, preferably an epoxy crosslinking agent having 2 to 6 epoxy groups. Specifically, the epoxy crosslinking agent can be at least one of trimethylolpropane triglycidyl ether (TMPTGE), 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane.

[0056] Further, the aziridine crosslinking agent includes at least one of 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine), trimethylolpropane tris[3-(2-methylaziridinyl)propionate] and pentaerythritol tris(3-aziridinyl)acrylate.

[0057] In a specific embodiment of the present invention, the polyacrylate emulsion is mainly prepared by emulsion polymerization of acrylic ester monomers in water.

[0058] In a specific embodiment of the present invention, the polyacrylate emulsion comprises the following components:

[0059]

[0060]

[0061] In a specific embodiment of the present invention, the soft monomer includes at least one of butyl acrylate, 2-ethylhexyl acrylate, ethyl acrylate and n-octyl acrylate. In the polyacrylate emulsion of the present invention, the soft monomer is used in an amount of 22 to 32 parts by mass, specifically 22 parts by mass, 25 parts by mass, 30 parts by mass, 32 parts by mass or any value between the two end values.

[0062] In a specific embodiment of the present invention, the hard monomer includes at least one of methyl methacrylate and isobornyl (meth)acrylate, wherein the isobornyl (meth)acrylate includes isobornyl acrylate and / or isobornyl methacrylate. In the polyacrylate emulsion of the present invention, the amount of the hard monomer is 14 to 21 parts by mass, specifically 14 parts by mass, 16 parts by mass, 18 parts by mass, 21 parts by mass, or any value between the two end values.

[0063] In a specific embodiment of the present invention, the functional monomer includes at least one of hydroxypropyl acrylate, hydroxyethyl acrylate and acrylic acid. In the polyacrylate emulsion of the present invention, the functional monomer is used in an amount of 4 to 9 parts by mass, specifically 4 parts by mass, 6 parts by mass, 8 parts by mass, 9 parts by mass or any value between the two end values.

[0064] The inventors of the present invention have found that by regulating the ratio of monomers and other components within the above-mentioned range, on the one hand, a certain amount of functional monomers such as carboxyl or hydroxyl groups can be introduced to bond with isocyanate curing agents and cross-linking agents to achieve curing and bonding with carboxyl-modified MXene; on the other hand, the mechanical properties of the conductive adhesive system can be guaranteed by compounding soft monomers and hard monomers.

[0065] In the polyacrylate emulsion of the present invention, the amount of deionized water is 47-53 parts by mass, and specifically can be 47 parts by mass, 50 parts by mass, 53 parts by mass or any value between the two end values.

[0066] In a specific embodiment of the present invention, the solid content of the polyacrylate emulsion is 45% to 55%, specifically 45%, 50%, 55% or any value between the two ends, and the solid content can be adjusted according to coating requirements.

[0067] In a specific embodiment of the present invention, the initiator includes a water-soluble initiator, including but not limited to persulfate, hydroperoxide, etc. For example, it can be ammonium persulfate, potassium persulfate, sodium persulfate, tert-butyl peroxyneoheptanoate, etc. In the polyacrylate emulsion of the present invention, the amount of the initiator is 0.3 to 0.4 parts by mass, specifically 0.3 parts by mass, 0.35 parts by mass, 0.37 parts by mass, 0.4 parts by mass, or any value between the two end values.

[0068] In a specific embodiment of the present invention, the emulsifier includes at least one of sodium lauryl sulfate, sodium alkyl sulfosuccinate and sodium salt of alkylphenol ether sulfosuccinate, but is not limited thereto. In the polyacrylate emulsion of the present invention, the amount of the emulsifier is 0.6 to 1.2 parts by mass, specifically 0.6 parts by mass, 0.8 parts by mass, 1.0 parts by mass, 1.1 parts by mass, 1.2 parts by mass or any value between the two end values.

[0069] In a specific embodiment of the present invention, the buffer comprises at least one of ammonium bicarbonate, sodium bicarbonate, sodium dihydrogen phosphate and sodium acetate. In the polyacrylate emulsion of the present invention, the amount of the buffer is 0.1 to 0.14 parts by weight, specifically 0.1 parts by weight, 0.12 parts by weight, 0.14 parts by weight or any value between the two end values.

[0070] In a specific embodiment of the present invention, the reducing agent includes at least one of ferrous salt, sodium bisulfite, sodium sulfite, sodium dithionite and sodium thiosulfate. Commercially available products can be used, such as Solpregain EC15 produced by Solpro of the Netherlands. In the polyacrylate emulsion of the present invention, the reducing agent is used in an amount of 0.14 to 0.16 parts by mass, specifically 0.14 parts by mass, 0.15 parts by mass, 0.16 parts by mass or any value between the two end values.

[0071] Other additives may also be added to the polyacrylate emulsion of the present invention, such as conventional additives such as defoamers and antistatic agents. Commonly used defoamers may be natural oils and their modified products, alcohols, synthetic fatty acids and fatty acid esters, amides, phosphates, polyethers and polyether-type nonionic surfactants, etc. Natural oils and their modified products such as vegetable oils such as cottonseed oil, castor oil, coconut oil, tall oil and hop oil, animal oils such as lard, beef and mutton oil, animal and plant waxes such as palm wax, beeswax and spermaceti; alcohols such as diethylhexanol, isooctyl alcohol, isopentanol, diisobutyl carbinol, etc.; synthetic fatty acids and fatty acid esters such as polyol fatty acid esters, such as ethylene glycol monostearate, glycerol monostearate, sorbitan esters, etc.; amides such as distearylethylenediamine, dipalmitoylethylenediamine and oleoyldiethylenetriamine condensate; phosphates such as tributyl phosphate, trioctyl phosphate and amyl phosphate organic ammonium salt. Commercially available products may also be used, such as those produced by Evonik Industries. Antifoam 2290. In the polyacrylate emulsion of the present invention, the amount of the defoamer is 0.01 to 0.05 parts by mass, specifically 0.01 parts by mass, 0.02 parts by mass, 0.05 parts by mass or any value between the two end values.

[0072] The present invention also provides a method for preparing the polyacrylate emulsion, wherein the polyacrylate emulsion is prepared by a pre-emulsification semi-continuous method. The pre-emulsification semi-continuous emulsion polymerization process is adopted in the present invention to prepare a polyacrylate emulsion with high stability, thereby improving the yield and product quality.

[0073] The pre-emulsification semi-continuous method includes:

[0074] The soft monomer, hard monomer and functional monomer in mass ratio, 85% to 90% of emulsifier and deionized water are mixed to obtain a pre-emulsion; 10% to 20% of the pre-emulsion and 40% to 60% of the initiator are added to the aqueous solution of the buffer and the remaining emulsifier, and after stirring evenly at 80 to 90° C., the remaining pre-emulsion and 10% to 20% of the initiator are added dropwise, and the reaction is stirred for more than 1 hour; the temperature is lowered to 55 to 65° C., the remaining initiator is added, and the reaction is stirred for more than 0.5 hour, and then a defoamer and a reducing agent are added and stirred evenly, and the pH is adjusted to neutral with ammonia water, and the reaction is stopped when the temperature is naturally lowered to room temperature to obtain a polyacrylate emulsion.

[0075] The second aspect of the present invention provides a water-based conductive pressure-sensitive adhesive, and the pressure-sensitive adhesive comprises the water-based conductive pressure-sensitive adhesive composition provided by the first aspect of the present invention.

[0076] The invention also provides a method for preparing the pressure-sensitive adhesive, which comprises the following steps: mixing the components in proportion and stirring evenly.

[0077] In a specific embodiment of the present invention, the mixing includes: mixing the carboxyl-modified MXene with deionized water, then mixing it with the polyacrylate emulsion, and then adding the isocyanate curing agent and the cross-linking agent, and mixing them evenly.

[0078] In actual operation, the mixing of each step can be carried out by ultrasound and / or stirring, which can further improve the dispersion uniformity of the carboxyl-modified MXene in the system. The duration of ultrasound and / or stirring is not limited and is routinely adjusted according to the uniformity of material mixing.

[0079] The third aspect of the present invention provides a pressure-sensitive adhesive product, which is made of the pressure-sensitive adhesive provided by the second aspect of the present invention, or contains the pressure-sensitive adhesive composition provided by the first aspect of the present invention.

[0080] The pressure-sensitive adhesive product of the present invention can be prepared into various forms such as labels, films, and tapes.

[0081] In practical application, it may include a release layer and a conductive adhesive layer arranged on one side of the release layer; the conductive adhesive layer is mainly made of the above-mentioned pressure-sensitive adhesive.

[0082] Among them, the release layer may include various conventional release layers. In actual operation, the conductive adhesive layer can be obtained by coating the pressure-sensitive adhesive on the surface of the release layer and drying and curing. Among them, the coating method is not limited, and roller coating, scraper coating or dip coating can be used. In actual operation, coating can be applied by a coater. The thickness of the release layer can be freely selected according to actual needs, without special limitations, for example, it can be set to 25 to 100 μm, specifically 25 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm or any value between the two ends.

[0083] In the conductive adhesive product of the present invention, the thickness of the conductive adhesive layer can be adjusted according to the actual application scenario. In the following examples, 1 g represents 1 part by mass.

[0084] Example 1

[0085] 1. Preparation of polyacrylate emulsion:

[0086] (1) Component composition: soft monomer: butyl acrylate, 24 g; hard monomer: methyl methacrylate, 16 g; functional monomer: acrylic acid 3.75 g, hydroxypropyl acrylate 4.5 g; initiator: ammonium persulfate 0.38 g; emulsifier: sodium dodecyl sulfate 0.7 g, sodium alkyl disulfonate succinate (A-501) 0.05 g, sodium salt of alkylphenol ether sulfosuccinate (MS-1) 0.05 g; buffer: ammonium bicarbonate 0.13 g; reducing agent: Solpregain EC15, 0.15 g; deionized water, 50 g; defoaming agent: TEGO Antifoam 2290, 0.045 g;

[0087] (2) Preparation method:

[0088] The above soft monomer, hard monomer, functional monomer, sodium dodecyl sulfate and half of the deionized water are added to a flask, and mixed evenly under high-speed shear stirring to obtain a uniformly dispersed pre-emulsion; the other half of the deionized water is added to a three-necked flask, the temperature is raised to 60° C., A-501 and MS-1 are added in a mass ratio under stirring, the temperature is raised to 75° C., 15% of the pre-emulsion is added, the temperature is raised to 85° C., half of the ammonium persulfate is added, and the mixture is stirred evenly. Then, the remaining amount of the pre-emulsion and 1 / 4 of the ammonium persulfate are added dropwise, and the temperature is maintained and stirred for 3 hours after the addition is completed; then the temperature is lowered to 60° C., 1 / 4 of the ammonium persulfate is added, stirring is continued for 40 minutes, and then the temperature is lowered to 50° C., TEGO Antifoam 2290 and Solpregain EC15 are added in mass parts, the mixture is stirred evenly, and the pH is adjusted to neutral with ammonia water, and the reaction is stopped by naturally lowering the temperature to room temperature to obtain a polyacrylate emulsion.

[0089] 2. Preparation of carboxyl-modified MXene:

[0090] (1) Weigh 4g of LiF and dissolve it in 100mL of hydrochloric acid (9mol / L), stir for 10min, slowly add 5g of Ti3AlC2 powder; stir at 35℃ for 24h to obtain a multilayer MXene dispersion. Wash with deionized water until neutral, then disperse the washed precipitate in 200mL of anhydrous ethanol, ultrasonically treat in an ice bath for 2.5h, disperse the precipitate in deionized water and centrifuge at a centrifugal speed of 4000r / min for 30min, collect and adjust the supernatant concentration to 4mg / mL, and obtain a MXene suspension;

[0091] (2) Weigh 2 g of chloroacetic acid and 3.4 g of sodium hydroxide and add them to 100 mL of the MXene suspension obtained in step (1), stir magnetically for 5 min, disperse the MXene evenly by ultrasound, introduce nitrogen into the solution for 20 min, and heat and stir the solution in a 60°C water bath under nitrogen protection for 12 h. Wash the mixed solution by centrifugation until it is neutral, collect the precipitate by centrifugation, and collect the carboxyl-modified MXene with a particle size of 50 μm through a mesh sieve.

[0092] 3. Preparation of water-based conductive pressure-sensitive adhesive:

[0093] (1) Components:

[0094] 50 g of the polyacrylate emulsion prepared in step 1;

[0095] 25 g of carboxyl-modified MXene prepared in step 2;

[0096] TDI, 1g;

[0097] 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine), 3.5 g;

[0098] 20.5g of deionized water.

[0099] (2) Preparation method:

[0100] The above-mentioned carboxyl-modified MXene and deionized water were mixed and ultrasonically dispersed for 30 minutes, and then the above-mentioned polyacrylate emulsion was added, stirred evenly, and ultrasonically dispersed for 30 minutes, and then the above-mentioned TDI and cross-linking agent were added in sequence, stirred evenly, to obtain a water-based conductive pressure-sensitive adhesive to be coated.

[0101] Example 2

[0102] This example is carried out with reference to Example 1, the only difference being that the raw material ratio of the water-based conductive pressure-sensitive adhesive is different, and the preparation method and other components are the same as those of Example 1, and the specific differences are as follows:

[0103] Water-based conductive pressure-sensitive adhesive includes the following components:

[0104] 40 g of polyacrylate emulsion, 20 g of carboxyl-modified MXene, 0.5 g of TDI, 2.8 g of 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine) and 36.7 g of deionized water.

[0105] Example 3

[0106] This example is carried out with reference to Example 1, the only difference being that the raw material ratio of the water-based conductive adhesive is different, and the preparation method and other components are the same as those of Example 1, and the specific differences are as follows:

[0107] Water-based conductive pressure-sensitive adhesive includes the following components:

[0108] Polyacrylate emulsion 55.1 g, carboxyl-modified MXene 35 g, TDI 5 g, 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine) 4.9 g.

[0109] Example 4 Group

[0110] This example group was carried out with reference to Example 1, except that the raw material ratio of the polyacrylate emulsion was different, and the preparation method and other components were the same as those of Example 1. The specific differences are as follows:

[0111] Example 4a: butyl acrylate 22g, methyl methacrylate 14g, acrylic acid 2g, hydroxypropyl acrylate 2g, ammonium persulfate 0.3g, sodium lauryl sulfate 0.5g, A-501 0.05g, MS-1 0.05g, ammonium bicarbonate 0.1g, SolpregainEC15 0.14g, deionized water 47g, TEGO Antifoam 2290 0.01g;

[0112] Example 4b: butyl acrylate 32 g, methyl methacrylate 21 g, acrylic acid 4 g, hydroxypropyl acrylate 5 g, ammonium persulfate 0.4 g, sodium lauryl sulfate 1.1 g, A-501 0.05 g, MS-1 0.05 g, ammonium bicarbonate 0.14 g, Solpregain EC15 0.16 g, deionized water 53 g, TEGO Antifoam 2290 0.05 g.

[0113] Example 5 Group

[0114] This example group was carried out with reference to Example 1, except that the amount of carboxyl-modified MXene was different, in order to verify the influence of the mass ratio of carboxyl-modified MXene to cross-linking agent on product performance. Due to the adjustment of the amount of carboxyl-modified MXene, in order to keep the total amount constant, the amount of deionized water was adjusted accordingly. The preparation method and other components were the same as those in Example 1, and the specific differences were as follows:

[0115] Example 5a: 21 g of carboxyl-modified MXene, a mass ratio of carboxyl-modified MXene to cross-linking agent of 6:1, and 24.5 g of deionized water;

[0116] Example 5b: 35 g of carboxyl-modified MXene, the mass ratio of carboxyl-modified MXene to cross-linking agent is 10:1, and deionized water is 10.5 g;

[0117] Example 5c: 14 g of carboxyl-modified MXene, a mass ratio of carboxyl-modified MXene to cross-linking agent of 4:1, and 31.5 g of deionized water;

[0118] Example 5d: 38.5 g of carboxyl-modified MXene, the mass ratio of carboxyl-modified MXene to cross-linker is 11:1, and 7 g of deionized water.

[0119] Example 6 Group

[0120] This example group was carried out with reference to Example 1, except that the mass of sodium hydroxide in the preparation of carboxyl-modified MXene was different. The preparation method and other components were the same as those in Example 1. The specific differences are as follows:

[0121] Example 6a: 2 g of sodium hydroxide, the mass ratio of chloroacetic acid to sodium hydroxide is 1:1;

[0122] Example 6b: 4 g of sodium hydroxide, the mass ratio of chloroacetic acid to sodium hydroxide is 1:2;

[0123] Example 6c: Sodium hydroxide 1g, mass ratio of chloroacetic acid to sodium hydroxide is 1:0.5;

[0124] Example 6d: 5 g of sodium hydroxide, the mass ratio of chloroacetic acid to sodium hydroxide is 1:2.5.

[0125] Example 7 Group

[0126] This example group was carried out with reference to Example 1, except that the particle size of the carboxyl-modified MXene was different. The preparation method and other components were the same as those in Example 1. The specific differences are as follows:

[0127] Example 7a: The particle size of carboxyl-modified MXene is 35 μm;

[0128] Example 7b: The particle size of carboxyl-modified MXene is 75 μm;

[0129] Example 7c: The particle size of carboxyl-modified MXene is 25 μm;

[0130] Example 7d: The particle size of carboxyl-modified MXene is 85 μm.

[0131] Example 8 Group

[0132] This example group was carried out with reference to Example 1, except that the concentration of the MXene suspension was different. The preparation method and other components were the same as those in Example 1. The specific differences are as follows:

[0133] Example 8a: The concentration of MXene suspension is 6 mg / mL;

[0134] Example 8b: The concentration of the MXene suspension is 8 mg / mL.

[0135] Comparative Example 1

[0136] This comparative example group was prepared with reference to Example 1, except that the addition of carboxyl-modified MXene in the pressure-sensitive adhesive was changed. The preparation method and other components were the same as those in Example 1, and the specific differences are as follows:

[0137] Comparative Example 1a: No carboxyl modification was performed on MXene, and only MXene powders of equal particle size and mass were added;

[0138] Comparative Example 1b: Silver powder of equal particle size and mass is used instead of carboxyl-modified MXene, and no cross-linking agent is included.

[0139] Comparative Example 2

[0140] This comparative example is carried out with reference to Example 1, except that the carboxyl-modified MXene in the pressure-sensitive adhesive is physically blended and not cross-linked with the pressure-sensitive adhesive, so no cross-linking agent is added, and the corresponding mass parts of deionized water are increased to keep the total amount constant. The preparation method and other components are the same as those in Example 1.

[0141] Test Case

[0142] In order to compare and illustrate the performance differences of the water-based conductive pressure-sensitive adhesives of different embodiments and comparative examples, the pressure-sensitive adhesives prepared in different embodiments and comparative examples were prepared as test samples by the following method, and the peel strength, holding force and volume resistivity were tested. The test results are shown in Table 1, and the test methods are referenced as follows.

[0143] Preparation of test samples: The pressure-sensitive adhesive prepared above was coated on the surface of a 50 μm PET release film, and placed in a 60° C. oven for aging for 48 hours to form a 300 μm conductive adhesive layer to obtain a test sample.

[0144] Peel strength: Use a peel force tester to test, refer to GB / T 2792-2014 "Test method for peel strength of adhesive tape", and use a steel plate for the test;

[0145] Holding force: Cut the test sample into 25mm×150mm specifications and pressurize it so that the contact area is 25mm×25mm. Use a universal material testing machine to test it, refer to GB / T 1450.2-2005 "Fiber reinforced plastic punching shear strength test method", and test the holding time (h) at 40℃ under a load of 1kg / min;

[0146] Volume resistivity: The volume resistivity of the conductive adhesive is tested using the four-probe method, and the test is carried out in accordance with GB / T31838.2-2019 "Dielectric and resistance properties of solid insulating materials Part 2: Resistance characteristics (DC method) Volume resistance and volume resistivity".

[0147] Table 1 Test results of different embodiments and comparative examples

[0148] serial number 180° peel strength / gf / 25mm Holding force / h <![CDATA[Volume resistivity / Ω·cm × 10 -6 > Example 1 2,540 >1,000 5.73 Example 2 2,650 >1,000 7.34 Example 3 1,980 >1,000 5.98 Example 4a 2,488 >1,000 5.84 Example 4b 2,577 >1,000 5.81 Example 5a 2,844 >1,000 6.55 Example 5b 2,366 >1,000 8.23 Example 5c 1,766 <1,000 145.6 Example 5d 980 <1,000 56.9 Example 6a 2,433 >1,000 5.88 Example 6b 2,505 >1,000 5.91 Example 6c 2,055 >1,000 80.3 Example 6d 1,975 >1,000 106.7 Example 7a 2,376 >1,000 5.98 Example 7b 2,144 >1,000 6.05 Example 7c 1,844 <1,000 66.7 Example 7d 1,467 <1,000 95.5 Example 8a 2,567 >1,000 5.81 Example 8b 1,833 <1,000 74.5 Comparative Example 1a 1,944 <1,000 175.6 Comparative Example 1b 1,344 <1,000 622.5 Comparative Example 2 1,807 <1,000 288.5

[0149] From the above test results, it can be seen that the water-based conductive pressure-sensitive adhesive of the present invention can improve the conductivity and ensure the bonding and mechanical properties of the pressure-sensitive adhesive by compounding the carboxyl-modified MXene with a cross-linking agent.

[0150] It can be seen from the test results of Example 5 that by limiting the range of the mass ratio of carboxyl-modified MXene to the cross-linking agent, the pressure-sensitive adhesive can have better performance; if the content of the carboxyl-modified MXene relative to the cross-linking agent is relatively low, the excess remaining cross-linking agent will react with the acrylic matrix to act as a curing agent, resulting in a decrease in the peeling force and retention of the conductive adhesive, and due to the low content of the carboxyl-modified MXene, the volume resistivity increases and the conductive performance decreases; if the content of the carboxyl-modified MXene relative to the cross-linking agent is relatively high, part of the carboxyl-modified MXene cannot be cross-linked and is in a free state, resulting in two-phase microphase separation and sedimentation, resulting in a decrease in the peeling force and retention of the pressure-sensitive adhesive, an increase in the volume resistivity, and a decrease in the conductive performance.

[0151] It can be seen from the test results of Example 6 that by limiting the range of the mass ratio of chloroacetic acid to sodium hydroxide, the number of modified carboxyl groups on MXene can be guaranteed, thereby making the pressure-sensitive adhesive have better performance; if the content of sodium hydroxide relative to chloroacetic acid is low, the excessive chloroacetic acid content will be over-neutralized with NaOH, the pH value of the reaction system will be reduced, and the alkaline conditions required for the nucleophilic substitution reaction cannot be provided, resulting in a significant decrease in the degree of MXene carboxyl functionalization, thereby resulting in a decrease in the adhesion and conductivity of the conductive adhesive; if the content of sodium hydroxide relative to chloroacetic acid is high, side reactions will occur due to the excessively high concentration of NaOH, such as the generation of impurities such as sodium glycolate, resulting in a decrease in the degree of MXene carboxyl functionalization and by-products, resulting in a decrease in the adhesion and conductivity of the conductive adhesive.

[0152] It can be seen from the test results of Example 7 that by limiting the particle size range of carboxyl-modified MXene, the pressure-sensitive adhesive can have better performance; if the particle size of the carboxyl-modified MXene is too low, the surface energy of the particles will increase, thereby reducing the dispersibility and causing aggregation, resulting in reduced conductivity, and agglomeration will also lead to reduced peeling force and retention; if the particle size of the carboxyl-modified MXene is too high, the conductive particles are unevenly distributed in the matrix, which can easily lead to interruptions in the conductive path, and excessively large particles may also affect the fluidity and adhesion of the conductive adhesive, resulting in increased resistance, thereby affecting the conductive properties of the conductive adhesive, and reducing the peeling force and retention.

[0153] It can be seen from the test results of Example 8 that by limiting the concentration range of the MXene suspension, the pressure-sensitive adhesive can have better performance; if the concentration of the MXene suspension is too high, the degree of MXene carboxyl functionalization decreases, and some MXene is not carboxyl functionalized, resulting in the inability to connect MXene and the pressure-sensitive adhesive through chemical bonds, which reduces the peeling force and retention force of the conductive adhesive, increases the resistivity, and reduces the conductive performance.

[0154] From the test results of comparative example 1, it can be seen that if MXene without carboxyl group is used, since MXene has no cross-linking sites, chemical bonds cannot be established between MXene and the organic matrix through the cross-linking agent, resulting in separation of the two phases, which reduces the peeling force and retention force; and it is impossible to construct a more effective conductive channel, which increases the resistivity and reduces the conductive performance; if silver powder is used as a conductive filler, it is not only easy to agglomerate, but also has strong rigidity and poor conductive performance.

[0155] From the test results of Comparative Example 2, it can be seen that if the carboxyl-modified MXene in the pressure-sensitive adhesive is physically blended without cross-linking, the physical blending causes the pressure-sensitive adhesive and the conductive particles to phase separate, the peel force and the holding force both decrease, and the volume resistivity increases, indicating that its conductive performance decreases. This may be because the carboxyl-modified MXene cannot be evenly mixed with the pressure-sensitive adhesive, resulting in partial sedimentation and agglomeration, causing the conductive performance to decrease.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A water-based conductive pressure-sensitive adhesive composition, characterized in that: The components include: Polyacrylate emulsion 40-60 parts by weight Carboxyl modified MXene 20-35 parts by mass Isocyanate curing agent 0.5-5 parts by weight Crosslinking agent 2-5 parts by weight Deionized water 0-38 parts by weight.

2. The water-based conductive pressure-sensitive adhesive composition according to claim 1, characterized in that: The mass ratio of the carboxyl-modified MXene to the cross-linking agent is (6-10):

1.

3. The water-based conductive pressure-sensitive adhesive composition according to claim 1 or 2, characterized in that: The carboxyl-modified MXene is prepared by modifying MXene, and the particle size of the carboxyl-modified MXene is 35 to 75 μm.

4. The water-based conductive pressure-sensitive adhesive composition according to claim 3, characterized in that: The preparation method of the carboxyl-modified MXene comprises: adding chloroacetic acid and sodium hydroxide to a MXene suspension in sequence for reaction, and collecting the resulting precipitate after the reaction to obtain the carboxyl-modified MXene; Wherein, the mass ratio of the chloroacetic acid to the sodium hydroxide is 1:(1-2).

5. The water-based conductive pressure-sensitive adhesive composition according to claim 1, characterized in that: The isocyanate curing agent includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate.

6. The water-based conductive pressure-sensitive adhesive composition according to claim 1, characterized in that: The cross-linking agent includes an epoxy cross-linking agent and / or an aziridine cross-linking agent; Preferably, the epoxy crosslinking agent includes an epoxy crosslinking agent containing 2 or more epoxy groups; Preferably, the aziridine crosslinking agent includes at least one of 1,1′-(1,3-phthaloyl)bis(2-methyl-aziridine), trimethylolpropane tris[3-(2-methylaziridinyl)propionate], and pentaerythritol tris(3-aziridinyl)acrylate.

7. The water-based conductive pressure-sensitive adhesive composition according to claim 1, characterized in that: The polyacrylate emulsion comprises the following components: Soft monomer 22-32 parts by weight Hard monomer 14-21 parts by weight Functional monomer 4-9 parts by weight Initiator 0.3-0.4 parts by mass Emulsifier 0.6-1.2 parts by mass Buffer 0.1-0.14 parts by mass Reducing agent 0.14-0.16 parts by mass Deionized water 47-53 parts by weight.

8. The water-based conductive pressure-sensitive adhesive composition according to claim 7, characterized in that: The soft monomer includes at least one of butyl acrylate, 2-ethylhexyl acrylate, ethyl acrylate and n-octyl acrylate; and / or, the hard monomer comprises at least one of methyl methacrylate and isobornyl (meth)acrylate; And / or, the functional monomer includes at least one of hydroxypropyl acrylate, hydroxyethyl acrylate and acrylic acid.

9. A pressure-sensitive adhesive, characterized in that: The pressure-sensitive adhesive comprises the water-based conductive pressure-sensitive adhesive composition according to any one of claims 1 to 8.

10. A pressure-sensitive adhesive product, characterized in that: The pressure-sensitive adhesive product is made of the pressure-sensitive adhesive described in claim 9, or is made of the water-based conductive pressure-sensitive adhesive composition described in any one of claims 1 to 8.